Visual word recognition of Chinese–Japanese bilinguals: limited role of phonology - Jiao, Zhongyan; Du, Leyi; Wang, Yifan; Li, Yixian (Frontiers in Psychology, 2024)
Introduction The investigation of how orthography and phonology influence lexical semantic access in visual word identification is a crucial area in psycholinguistics. Previous studies, focusing on alphabetic scripts in bilingual lexical recognition, have highlighted the facilitative role of phonological similarity. Yet, the impact of cross-language phonological similarity in bilinguals using non-alphabetic scripts remains unclear. Methods In this study, we employed a lexical decision task to examine Chinese–Japanese bilinguals. Participants were presented with Chinese–Japanese cognate translation pairs, categorized into phonologically similar and dissimilar cognates. Results Analysis of event-related potentials (ERP) revealed no significant differences between phonologically similar and dissimilar contexts in the early time windows (90–170 ms and 170–270 ms). However, in the later time window (350–500 ms), significant differences were observed, with the phonologically dissimilar condition eliciting a larger negative wave. Discussion Contrary to findings in alphabetic script-based studies, our results suggest that in logographic script processing, the activation of phonology and semantics occurs simultaneously, and the influence of phonology is limited. This indicates a distinct cognitive processing mechanism in non-alphabetic language bilinguals, providing new insights into the dynamics of bilingual lexical recognition.